ANALISIS PENGARUH PEMERINTAH TERHADAP INDEKS PEMBANGUNAN MANUSIA DI JAWA TIMUR - Aviyati, Syivai (IQTISHODUNA, 2014)
Human development has always been as the main topic of sustainable development. Improving thehuman quality as responsibility of all people, especially the government in term of allocation roles to providedifferent types of services such as education facilities, health and road infrastructure. The Social indicators tomeasure the success of human development used the human development index. This study empiricallyanalyze the effect of health expenses, education and road infrastructure as well as the growth of the populationas a control variable to the index of human development in the District/City of East Java. Data were collectedfrom 29 districts and 9 Cities of the year 2007–2012. To analyze the panel data of district/City, we use a fixedeffect model (FEM). We found a statistically significant and positive effect between government expenses oneducation and government expenses in the health sector to the index of human development, while governmentexpenses in infrastructure and population growth have no significant influence to the index of humandevelopment but have a positive direction.